2022
DOI: 10.3390/ijerph191811321
|View full text |Cite
|
Sign up to set email alerts
|

20 Years of ICF—International Classification of Functioning, Disability and Health: Uses and Applications around the World

Abstract: The International Classification of Functioning Disability and Health (ICF) was approved in 2001 and, since then, several studies reported the increased interest about its use in different sectors. A recent overview that summarizes its applications is lacking. This study aims to provide an updated overview about 20 years of ICF application through an international online questionnaire, developed by the byline authors, and sent to each World Health Organization Collaborating Centers of the Family of Internation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 31 publications
0
42
0
10
Order By: Relevance
“…The respondents in our study reported needing information about function rather than diagnoses, which mirrors a paradigm shift in areas of research in child disability and health using the ICF framework (International Classification of Functioning, Disability and Health). 12 They report on the impact lung disease has on their child's function (and often the function of the whole family) rather than report a diagnosis. Informing parents in the NICU that their extremely preterm infant has a diagnosis of chronic lung disease, or BPD, may not be very useful.…”
Section: Discussionmentioning
confidence: 99%
“…The respondents in our study reported needing information about function rather than diagnoses, which mirrors a paradigm shift in areas of research in child disability and health using the ICF framework (International Classification of Functioning, Disability and Health). 12 They report on the impact lung disease has on their child's function (and often the function of the whole family) rather than report a diagnosis. Informing parents in the NICU that their extremely preterm infant has a diagnosis of chronic lung disease, or BPD, may not be very useful.…”
Section: Discussionmentioning
confidence: 99%
“…The biopsychosocial model was later introduced to address the limitations of the medical model in recognizing the psychological, social, and behavioral dimensions of a medical condition ( 43 , 44 ), and became the focus of the ICF. However, the ICF was never intended to replace the medical model but to enhance it ( 45 ). While it may be easier to elicit functional difficulties through household surveys, such responses do not provide a pathway for the effective care of children with disabilities within the health systems ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…The usage of technologies in the different instruments to evaluate disability, such as wearables [ 86 ] or optoelectronic systems [ 34 ], for assessing ICF domains could improve the objectivity of the measures, be cost-effective and decrease assessment time. Even the implementation of the ICF coding itself can be improved by using health technology [ 103 ], as its information technology infrastructure for documenting, coding, and reporting has been identified as poor [ 104 ]. There were several indicators, and instruments, that presented an association with age only in one of the included studies.…”
Section: Discussionmentioning
confidence: 99%